Promotion of tumor progression by exosome transmission of circular RNA circSKA3 - William W. Du; Xiangmin Li; Jian Ma; Ling Fang; Nan Wu; Feiya Li; Preet Dhaliwal; Weining Yang; Albert J. Yee; Burton B. Yang (Elsevier, 2022)
We performed in vitro and in vivo experiments to investigate the role of the circular RNA circSKA3 in tumor development. We examined the effects of circSKA3 on mediating breast cancer metastasis. In vitro, we found that the circular RNA circSKA3 was transferred between breast cancer cells, which were decreased by inhibiting exosome secretion. In vivo, circSKA3-containing exosomes potentiated tumor development and invasion that were inhibited by blocking exosome transmission. The ascites isolated from tumor-bearing mice or breast cancer patients showed high levels of circSKA3 and integrin β1. Single-cell culture and single-cell PCR showed that circSKA3 was heterogeneously expressed, the cells expressing higher levels of circSKA3 had a higher potential to form large colonies. This property was similar to c-myc, but circSKA3 expression had no correlation with c-myc levels. The effects of circSKA3 on cell migration and invasion appeared to predominate c-myc functions. By releasing circSKA3-containing exosomes to cancer cells expressing lower levels of circSKA3, the large colonies could regulate the activities of small colonies, enhancing the tumor-forming capacity of the entire population. Thus, we provide evidence that the transmission of circular RNAs in tumor-derived exosomes may allow for the maintenance of advantageous invasive sub-clones in breast cancer.